Global perspective of inclusive education, in Chile and south american main countries - Esparza Manríquez, Romina (2019)
Literature review demonstrates the challenge that the educational system faces in connection with a model of inclusion. Inclusive pedagogy is mentioned, targeting all students, specially, those who has been excluded from educational opportunities, such as kids that present some type of Special Educational Needs. In this context and taking into account the current public policies, it is necessary to review the current context, both in Chile and South American countries, envisage these new proposals. In spite of all the laws and proclamations, it is established that the main problems reside in the scarce teacher training for the attention of diversity, lack of resources destined to special education and persistence of segregating students with different capabilities being necessary to reformulate the regulation that governs the inclusion of these children to the society.